OPTIMALISASI PRODUKSI NILAM MELALUI APLIKASI PUPUK ORGANIK BERBASIS LIMBAH PERTANIAN PADA KELOMPOK PETANI NILAM HARAPAN BARU DI KABUPATEN BUTON UTARA - Ridwan Ridwan; La Aman Tabia; La Ode Zainudin; Kamelia Kamelia; Ayu Ayu (Devote: Jurnal Pengabdian Masyarakat Global, 2026)
Pogostemon cablin (patchouli) is an essential oil–producing plant with high economic value, widely used in the perfume, cosmetic, and pharmaceutical industries. North Buton Regency has strong potential for patchouli development, particularly through the Harapan Baru Patchouli Farmers Group. However, patchouli cultivation still faces challenges due to dependence on expensive and often scarce chemical fertilizers, which also negatively affect soil fertility and the environment. This community service program was designed to increase patchouli productivity through the utilization of organic fertilizers derived from agricultural waste while simultaneously strengthening the institutional capacity of the farmer group. Activities included problem identification through field observation, coordination with relevant stakeholders, and socialization sessions to enhance farmers’ understanding and motivation. Technology implementation was carried out through training on the production of organic fertilizers, application of fertilizers to crops, organic-based patchouli maintenance, and institutional strengthening through management, administrative, and partnership development training. Continuous mentoring and periodic evaluation were conducted to assess farmers’ knowledge, skills, and the impact of organic fertilizer use on plant growth. The results showed significant improvements: farmers’ understanding of organic fertilizers increased from 30% to 90%, their ability to produce solid and liquid organic fertilizers improved by more than 60%, and patchouli production reached approximately 200 kg per month. The use of organic fertilizers increased patchouli oil productivity by 10–20%, with better distillation quality (clearer color, softer aroma, and higher yield). Institutionally, active membership increased by 75%, financial reporting capacity improved by 70%, and the organizational structure became more defined through formal bylaws and standard operating procedures. Overall, the program successfully fostered group self-reliance, strengthened member solidarity, and promoted an environmentally friendly and economically valuable sustainable agricultural system.